Molecular Docking Study of Isoxazole Indole Derivatives (B2A2 Series) as Promising Selective Estrogen Receptor Modulators & Anticancer Drugs - Iyer, Jayashree Monikanta; Khare, Aradhana; Pandey, Jaya; Yadav, Manish (Drug Research, 2022)
A series of 7 compounds with isoxazole – indole – γ-resorcylic acid scaffold, segregated into B2 & A2 series, wherein, B2 comprises Compounds: 13, 14, 15 & 16 and A2 comprises Compounds: 10, 11 & 12, on the basis of the variable substituents at the indole, resorcinol and isoxazole end of the scaffold as in Figure: 1, were designed and docked with human estrogen receptor: 1ERRα. The Binding affinity (BA) and the interacting amino acids compared with reference selective estrogen receptor modulators (SERM’s) such as Raloxifene, Estradiol, Bazedoxifene, Bisphenol, Genistein, Daidzein, Ormiloxifene, Tamoxifen, 6-hydroxy-naphthalen-2yl-benzo(D)-isoxazol-6-ol(1) using PyRx software and their ADME properties predicted with SWISS ADME online tool. Significant similarities and minor differences in the binding pattern between the key interacting aminoacids such as Arg 394, Glu 353, Asp 351, Leu 346, Leu 525, Trp 383, Phe 404, Ala 350, Leu 387, Met 421 responsible for ER agonist/antagonist affinity found in the binding cavity of a 1 Errα -Bazedoxifene/1 Errα -raloxifene/1 Errα -estradiol docked complex AND 1 Errα -isoxazole-indole- resorcinol docked complex indicate their promising potential to serve as potent ER agonists in bone or ER antagonists against breast cancer and other cancer diseases. The Compounds with highest BA is of the order: BA (A1series)>B1series>/<BA(A2 series)>/=BA (B2 series) exceptions: compounds: 4, 5 of B1 series & compound:13 of B2 series with identical and least BA values.BA(6)=BA(8)>BA(7)>BA(2)>BA(9)=BA(1)>BA(12)>BA(10)=BA(15)=BA(11)=BA(3)>BA(14)=BA(16)>BA(4)=BA(5)=BA(13).
Keywords: Molecular docking; Estrogen receptor; isoxazole indole resorcinol; binding affinity